Generation of virtual monochromatic CBCT from dual kV/MV beam projectionsa). Issue 12 (19th November 2013) - Li, Hao; Liu, Bo; Yin, Fang‐Fang
Abstract : Purpose: : To develop a novel on‐board imaging technique which allows generation of virtual monochromatic (VM) cone‐beam CT (CBCT) with a selected energy from combined kilovoltage (kV)/megavoltage (MV) beam projections. Methods: : With the current orthogonal kV/MV imaging hardware equipped in modern linear accelerators, both MV projections (from gantry angle of 0°–100°) and kV projections (90°–200°) were acquired as gantry rotated a total of 110°. A selected range of overlap projections between 90° to 100° were then decomposed into two material projections using experimentally determined parameters from orthogonally stacked aluminum and acrylic step‐wedges. Given attenuation coefficients of aluminum and acrylic at a predetermined energy, one set of VM projections could be synthesized from two corresponding sets of decomposed projections. Two linear functions were generated using projection information at overlap angles to convert kV and MV projections at nonoverlap angles to approximate VM projections for CBCT reconstruction. The contrast‐to‐noise ratios (CNRs) were calculated for different inserts in VM CBCTs of a CatPhan phantom with various selected energies and compared with those in kV and MV CBCTs. The effect of overlap projection number on CNR was evaluated. Additionally, the effect of beam orientation was studied by scanning the CatPhan sandwiched with two 5 cm solid‐water phantoms on both lateral sides and an electronic density phantom with two metal bolt inserts. Results: : Proper selection of VM energy [30 and 40 keV for low‐density polyethylene (LDPE), polymethylpentene, 2 MeV for Delrin] provided comparable or even better CNR results as compared with kV or MV CBCT. An increased number of overlap kV and MV projection demonstrated only marginal improvements of CNR for different inserts (with the exception of LDPE) and therefore one projection overlap was found to be sufficient for the CatPhan study. It was also evident that the optimal CBCT image quality was achieved when MV beams penetrated through the heavy attenuation direction of the object. Conclusions: : A novel technique was developed to generate VM CBCTs from kV/MV projections. This technique has the potential to improve CNR at selected VM energies and to suppress artifacts at appropriate beam orientations.